The Absorption of Vocational Education Graduates in The Automotive Sector in The Industrial World - Kurniawan, Rio; Jaedun, Amat; Mutohhari, Farid; Kusuma, Wahyu Mustafa (Journal of Education Technology, 2021)
The absorption of graduates in the industrial world is an important aspect that affects the quality of vocational high schools (SMK). However, the problem that occurs is the low absorption. This study aims to analyze the level of absorption of SMK graduates in light vehicle engineering (TKR) and motorcycle engineering and business (TBSM) programs. Descriptive research uses a quantitative approach to measure the percentage of graduate absorption. A total of 4 vocational high school job fairs were involved in this study. Techniques and instruments of data collection using methods and observation sheets by observing survey data in special job fairs. The data analysis technique used quantitative descriptive analysis and inferential analysis of the sample independent t test. The results showed that the level of absorption of SMK graduates in the TKR and TBSM majors was low. Various efforts to revitalize vocational education must be matured again. The link and match program of SMK with the industrial world needs to be more intensive to align the competencies taught to the competency needs of the industrial world, so that the absorption of graduates can be improved.